2019
DOI: 10.3390/ijerph16183353
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear and Spatial Effects of Tourism on Carbon Emissions in China: A Spatial Econometric Approach

Abstract: Reducing carbon emissions is crucial to the sustainable development of tourism. However, there are no consistent conclusions about the nexus between tourism and carbon emissions. Considering the possible nonlinear and spatial effects of tourism on carbon emissions, this paper employed spatial econometric models combined with quadratic terms of explanatory variables to explore the nexus between them using Chinese provincial panel data from 2003 to 2016. The main results are as follows: (1) There is a significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 63 publications
(107 reference statements)
1
20
0
Order By: Relevance
“…Bi combined with the spatial econometric model to discuss the impact of tourism on carbon emissions. It is found that there is a significant inverted “U” shaped relationship between them, and tourism has an obvious spatial lag effect on carbon emissions, which is also an inverted “U” shaped relationship [ 38 ]. Paramati used panel econometric techniques to find that tourism played an important role in promoting economic growth, while tourism’s effect on CO 2 was largely dependent on sustainable tourism policies [ 39 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bi combined with the spatial econometric model to discuss the impact of tourism on carbon emissions. It is found that there is a significant inverted “U” shaped relationship between them, and tourism has an obvious spatial lag effect on carbon emissions, which is also an inverted “U” shaped relationship [ 38 ]. Paramati used panel econometric techniques to find that tourism played an important role in promoting economic growth, while tourism’s effect on CO 2 was largely dependent on sustainable tourism policies [ 39 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…For instance, 1% of increase in tourism revenue contributes to the 0.105% reduction of CO 2 emissions [30], and the developing countries have slower reduction speeds than the developed countries [31]. Furthermore, being considered as the low-carbon industry [32], tourism activities contribute to the upgrade of industrial structures and the renewal of urban functions, which helps better air environment protection [33,34]. Cases from the regions characterized as the traditional manufacturing industry centers prove that tourism industry, as a new economy growth mode, contributes to restructuring of the urban functional structures and to the protection of the air environment [35,36].…”
Section: E Effects Of Tourism On Air Environmentmentioning
confidence: 99%
“…Scientists from around the world are expected to work on more detailed analyses as satellite data or images have many uncertainties ( Schwandner et al, 2017 ). Another reason is that recent emerging studies lose sight on the presence of spillover effects and regional effects in air pollution ( Bi and Zeng, 2019 ; Chen et al, 2016 ; Du et al, 2020 ; Feng et al, 2020 ; Gong and Zhang, 2017 ; Yue et al, 2019 ; Zeng et al, 2019 , 2021 ), which may invalidate the results ( Kolak and Anselin, 2019 ). Many questions remain, including: Do spillover effects in air pollution exist in China during the pandemic?…”
Section: Introductionmentioning
confidence: 99%